The end of the wasp season : a novel - Mina, Denise (Mina, Denise. Alex Morrow novel., 2011)
When a notorious millionaire banker hangs himself, his death attracts no sympathy. But the legacy of a lifetime of selfishness is widespread, and the carnage most acute among those he ought to be protecting: his family. Meanwhile, in a wealthy suburb of Glasgow, a young woman is found savagely murdered. The community is stunned by what appears to be a vicious, random attack. When Detective Inspector Alex Morrow, heavily pregnant with twins, is called in to investigate, she soon discovers that a tangled web of lies lurks behind the murder. It's a web that will spiral through Alex's own home, the local community, and ultimately right back to a swinging rope, hundreds of miles away.